Danube Territorial Strategies: Array - Panaitescu, Manuela (Journal of Danubian Studies and Research, 2022)
The Danube region has been particularly affected by the economic consequences of the pandemic, so the recovery of the region's economy requires increased attention. The purpose of this article is to analyze the possibilities of financing through the Danube Transnational Program 2021-2027. It continues the previous research dedicated to the management of the projects implemented through the financing programs dedicated to the Danube Region. All the measures described in the program are based on the territorial strategy and must be seen in the broader context of existing strategic frameworks, such as the EUSDR (especially for PA7, PA8 and partly PA9), the Territorial Agenda 2030, the New Leipzig Charter, Recovery and Resilience Facility and the European Green Agreement.